Analisis Keterampilan Proses Sains Siswa Kelas IV SDN Kemayoran 1 Bangkalan - Riski Yasinia, Amira; Ika Dian Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the implementation of project-based learning by teachers without clear guidelines or indicators to assess science process skills (SPS). As a result, teachers had difficulty identifying the types of SPS that emerged during the project, while students' initial SPS scores were relatively low. The purpose of the study was to determine the SPS of grade IV students at SDN Kemayoran 1 Bangkalan. This study used a descriptive qualitative approach, which aims to describe the characteristics of objects on a limited scale and in a short time, so that the results cannot be generalized. Data collection techniques were in the form of observation triangulation, interviews, and documentation. Data analysis was carried out through data reduction, presentation, and drawing conclusions or verification. The results showed that students' science process differences in achievement are also seen based on the level of student ability, where students with high and medium abilities both show weaknesses in the indicators of asking questions and observing, while students with low abilities have difficulty in the indicators of asking questions, formulating hypotheses, observing, and interpreting data. This finding indicates that students' science process skills have developed well through project activities, but special strengthening is still needed in several indicators, especially in forming scientific questions and developing careful observation skills.